Public Administration in Germany - Kuhlmann, Sabine; Proeller, Isabella; Schimanke, Dieter; Ziekow, Jan (Governance and Public Management, 2021)
This open access book presents a topical, comprehensive and differentiated analysis of Germany's public administration and reforms. It provides an overview on key elements of German public administration at the federal, Länder and local levels of government as well as on current reform activities of the public sector. It examines the key institutional features of German public administration; the changing relationships between public administration, society and the private sector; the administrative reforms at different levels of the federal system and numerous sectors; and new challenges and modernization approaches like digitalization, Open Government and Better Regulation. Each chapter offers a combination of descriptive information and problem-oriented analysis, presenting key topical issues in Germany which are relevant to an international readership.